2019
DOI: 10.21608/jtcps.2019.14878.1024
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and thermodynamics of aniline blue adsorption onto cross-linked gelatin/chitosan polymer blends

Abstract: ILMS of cross-linked gelatin/chitosan blends have been successfully synthesized using glutaraldehyde as a cross-linker. The synthesized samples were characterized using infrared Fourier transformation (FT-IR), and X-ray diffraction (XRD). The solubility in aqueous media, the pH-responsive swelling and point of zero surface charge were explored. The adsorption efficiency of samples for the removal of the anionic dye aniline blue from aqueous media has been studied. The parameters that affect the adsorption effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…10) kinetic model. The R 2 value is higher than the R 1 value indicating that the results show better acceptance to pseudo-second order models, this in agreement with Okasha et al (2019). Hence, the copper adsorption belongs to pseudo-second order.…”
Section: -Results and Discussionsupporting
confidence: 82%
“…10) kinetic model. The R 2 value is higher than the R 1 value indicating that the results show better acceptance to pseudo-second order models, this in agreement with Okasha et al (2019). Hence, the copper adsorption belongs to pseudo-second order.…”
Section: -Results and Discussionsupporting
confidence: 82%
“…The positive value of ΔS o reveals an increase in the degree of randomness for all tested carbons at the solidsolution interface for MB adsorption. Previous studies showed similar trends for MB adsorption [43][44][45].…”
Section: Thermodynamic Parameterssupporting
confidence: 58%
“…aniline blue (AB) (Kumar and Tamilarasan 2013). Aniline blue is implicated in irritation of the gut, shortness of breath and coughing (Koyuncu and Kul 2019;Okasha et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Adsorbents of various types have been the subject of keen investigation for the removal of water pollutants. These adsorbents include clay (El Mouzdahir et al 2007), polymers (Moawed et al 2015;Okasha et al 2019), nanocomposites (Kaplan and Kasgoz 2011;Hasanzadeh et al 2020), activated carbon (Amin 2009;Solgi et al 2017), biomass (Jia et al 2017;Baysal et al 2018) and biowastes such as coffee (Wong et al 2020), bark waste (Silva et al 2018) and peels of various fruits such as grapefruit, orange, lemon, jackfruit, litchi, pomegranate, melons, banana, guava, mango, pineapple (Pathak et al 2015). Other agro-based (by-products) such as stem, leaves and root also have excellent potential for removal of both ionic and non-ionic dyes from wastewater (Mishra et al 2021).…”
Section: Introductionmentioning
confidence: 99%